Mechanisms for the sustainable development of agricultural enterprises in Кazakhstan: the impact of digitalisation and investment - Akynov, D.M.; Lambekova, А.N.; Nurgaliyeva, A.M. (Journal of Economic Research & Business Administration, 2025)
Digital transformation of agriculture has become a key factor in improving productivity, sustainability and competitiveness in many countries, including Kazakhstan. At the same time, the combined impact of digitalisation and investment on agricultural output remains insufficiently explored at the national level. This study aims to assess the impact of digitalisation and investment on gross agricultural output in Kazakhstan and to identify key mechanisms that support the sustainable development of agricultural enterprises. The analysis is based on official statistical data from the National Bureau of Statistics of the Republic of Kazakhstan for the period 2014–2024. Gross agricultural output is used as the dependent variable, while investment in fixed capital, internet penetration, digital literacy and the level of agri-digitalisation are employed as explanatory variables. Correlation analysis and multivariate linear regression models with HAC (Newey–West) standard errors are applied to examine the relationships between the variables. Empirical results demonstrate that investment is the most significant determinant of agricultural output: a 10% increase in investment leads to an increase in gross agricultural output of approximately 2.8–3.0%. Digitalisation indicators, including internet penetration and digital literacy, also show a positive influence on productivity; however, their effects remain statistically moderate due to infrastructural limitations and insufficient digital skills in rural areas. Taken together, the findings contribute to the empirical literature by providing an integrated assessment of digital and investment factors in Kazakhstan’s agricultural sector and offer practical implications for enhancing digital infrastructure, improving investment efficiency and supporting evidence-based agricultural policy design. Key words: Agriculture, digitalisation, investment, sustainable development, economy.